2013
DOI: 10.1112/s0010437x13007367
|View full text |Cite
|
Sign up to set email alerts
|

Braid group actions via categorified Heisenberg complexes

Abstract: Abstract. We construct categorical braid group actions from 2-representations of a Heisenberg algebra. These actions are induced by certain complexes which generalize spherical (Seidel-Thomas) twists and are reminiscent of the Rickard complexes defined by Chuang-Rouquier. Conjecturally, one can relate our complexes to Rickard complexes using categorical vertex operators.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…However, an analogue of [CLS,Prop. 4.7], can be used to show that there is a unique way (up to homotopy) to choose these multiples so that (18) becomes a complex.…”
Section: Aside: Complexes and Projectorsmentioning
confidence: 99%
“…However, an analogue of [CLS,Prop. 4.7], can be used to show that there is a unique way (up to homotopy) to choose these multiples so that (18) becomes a complex.…”
Section: Aside: Complexes and Projectorsmentioning
confidence: 99%
“…More recently, autoequivalences of the (bounded) derived categories D b (X [n] ) of the Hilbert schemes were intensively studied; see [Plo07], [Add11], [PS12], [Mea12], [Kru13], [CLS14], [KS14]. In particular, Addington [Add11] defined the notion of a P n -functor as a Fourier-Mukai transform F : D b (M ) → D b (N ) between derived categories of varieties with rightadjoint F R : D b (N ) → D b (M ) and the main property that In [Kru13] it was shown that for every smooth surface X and n ≥ 2 there is a P n−1 -functor H 0,n := H : D b (X) → D b…”
Section: Introductionmentioning
confidence: 99%
“…(b) We expect that the categorical braid group actions of [CLS14] can be generalized to the setting of the current paper.…”
mentioning
confidence: 99%